Study of the neutral mesons in Pb-Pb collisions at √2NN=2.76 TeV in the ALICE experiment at LHC - Leardini, Lucia (Journal of physics. Conference Series, 2015)
The π0 and η meson production in Pb-Pb collisions at =2.76 TeV is studied with the ALICE experiment at the LHC. The π0 meson invariant yields and nuclear modification factor R AA are presented here in six centrality classes. The results are obtained using the Photon Conversion Method (PCM) and utilizing the PHOS detector, for the transverse momentum range 0.4 < p T < 12 GeV/c. The π0 meson R AA is studied in different centrality classes and compared with results from experiments at lower energies, as a function of transverse momentum. The η meson production is studied using the PCM and utilizing the EMCal detector. The combination of these two independent methods will make possible the measurement of the η differential invariant cross section as a function of transverse momentum from 1 to 22 GeV/c in different centrality classes.
Im Titel befinden sich die Zeichen 2NN unterhalb des Wurzelzeichens und die Ziffer 2 erscheint hochgestellt
Gesehen am 15.06.2020